Association of Parenting Style and Mindful Eating with Sodium Intake among Adolescents in Indonesia - Pamungkas, Rizqy Amanatul Husna; Prafiantini, Erfi; Chandra, Dian Novita (UI Scholars Hub, 2023)
Background: Most adolescents have an excessive sodium intake associated with hypertension and cardiovascular disease (CVD). Parents have an important role in controlling adolescents’ nutritional intake, including sodium, through healthy eating. Mindful eating is considered healthy eating with the potential to control nutritional intake. This study aims to analyze the association of parenting style and mindful eating with sodium intake among adolescents. Methods: This cross-sectional study involved adolescents aged 15–18 years. Sodium intake was measured by repeated 24-hour food recall. Parenting style was examined with a validated parenting style and dimensions questionnaire self-administered by the adolescent parent. Mindful eating was evaluated using a mindful eating questionnaire (MEQ) self-administered by the adolescent. Data were analyzed using Kruskal–Walls and Spearman correlation. Results: Parenting style has no significant association with sodium intake, and mindful eating has a negatively significant correlation with sodium intake (p < 0.05; r = −0.17). Conclusions: Parenting style has no direct association with sodium intake. However, mindful eating has a significant association with sodium intake and parenting style. Mindful eating shows potential as a mediator between parenting style and sodium intake.